Regioselective Substitution of Vinyl Halide by n-Alkyl Mercaptans and Subsequent Reactions with Versatile Cyclic Secondary Amines - Ibis, Cemil; Fatih Tuyun, Amaç; Aydinli, Göksin (Asian Journal of Chemistry, 2010)
Herein, we have described the preparation of several S-subtituted nitrobuta-1,3-dienes (3a-b) using the 4-bromo-1,1,3,4-tetrachloro-2-nitrobuta-1,3-diene (1) with mercaptans (2a-b). Afterwards, N,S-substituted nitrobuta-1,3-diene compounds (5a, 7b and 9a-j) are obtained from the interaction of versatile secondary amines with the substituted product S-substituted nitrobuta- 1,3-dienes (3a-b) in dichloromethane. Synthesized compounds have been characterized by using IR and NMR spectroscopy methods. Structural characterization is supported by elemental analysis and by mass spectrometry with accurate mass measurement of the molecular ion.